2011
DOI: 10.1108/02634501111138554
|View full text |Cite
|
Sign up to set email alerts
|

Branding and product evaluation across Chinese regions

Abstract: PurposeThis paper aims to explore two fundamental aspects of branding in emerging markets. First, are there significant differences in product evaluation behaviour between regions within a large emerging market such as China? Second, how important is branding relative to other product cues in the product evaluation among consumers in emerging markets?Design/methodology/approachData were collected from a sample of respondents in three Chinese cities (Hong Kong, Shanghai, and Chongqing). Respondents were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This sector serves sophisticated consumers who are experienced and demanding (Chan et al, 2016) and also receptive to innovative technology with high economic status and education (Lee, 2014). Consumers are equipped with significant knowledge of international brands (Tam and Elliott, 2011), including the major smartphone brands (the focal product category in this study), which are available in major retail outlets.…”
Section: Data Collection and Samplementioning
confidence: 99%
“…This sector serves sophisticated consumers who are experienced and demanding (Chan et al, 2016) and also receptive to innovative technology with high economic status and education (Lee, 2014). Consumers are equipped with significant knowledge of international brands (Tam and Elliott, 2011), including the major smartphone brands (the focal product category in this study), which are available in major retail outlets.…”
Section: Data Collection and Samplementioning
confidence: 99%
“…First, findings show that brand source partially moderates the country-of-origin image/consumer brand evaluation relationship, although the subgroup analysis revealed that global brands receive more favorable ratings from consumers than local brands (Tam and Elliot, 2011). Research has shown that factors such as xenocentrism and cosmopolitanism may account for these preferences and evaluative judgments (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Hong Kong is an international city with a competitive, free-market economy (Barnes et al , 2009) and a well-developed retail sector (Liao and Shi, 2009). Hong Kong consumers are knowledgeable of international brands (Tam and Elliott, 2011), and particularly the major smartphone brands in the focal product category, which were available in major Hong Kong retail outlets. Hong Kongers are also regular users of social media, such as Facebook (Chan and Guillet, 2011; Cheung et al , 2011; Ng, 2016).…”
Section: Methodsmentioning
confidence: 99%